2021
DOI: 10.30901/2658-6266-2020-4-o3
|View full text |Cite
|
Sign up to set email alerts
|

Nomenclatural standards, voucher specimens and genetic passports of potato cultivars created in the Siberian and Ural breeding centers

Abstract: The present paper discusses methodological approaches to the creation of nomenclatural standards and genetic passports for Russian cultivars, currently being developed at the N.I. Vavilov Institute of Plant Genetic Resources (VIR) in collaboration with different breeding research centers. Plant material of potato cultivars bred in the Siberian Research Institute of Plant Cultivation and Breeding was collected by the cultivar creator A.D. Safonova in the experimental field of this institute and transferred to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 30 publications
0
5
0
1
Order By: Relevance
“…According to A. Barone with colleagues (1990) [84], a major dominant gene Gro1 confers resistance to all pathotypes of G. rostochiensis including Ro5. In our previous research it was shown the extremely low frequency of the Gro1-4 marker in the Russian cultivar genepool [42,[56][57][58][59]. A few Gro1-4-positive cultivars were involved in the present study, however, any association with resistance to Ro5 pathotype was not detected.…”
Section: Discussionmentioning
confidence: 49%
See 4 more Smart Citations
“…According to A. Barone with colleagues (1990) [84], a major dominant gene Gro1 confers resistance to all pathotypes of G. rostochiensis including Ro5. In our previous research it was shown the extremely low frequency of the Gro1-4 marker in the Russian cultivar genepool [42,[56][57][58][59]. A few Gro1-4-positive cultivars were involved in the present study, however, any association with resistance to Ro5 pathotype was not detected.…”
Section: Discussionmentioning
confidence: 49%
“…The obtained results indicated high (87%) predictive association between the presence of two markers of the H1 gene-57R and TG689-and phenotypic resistance to Ro1. The diagnostic value of these markers can be increased up to 90% in the case of counting moderately resistant cultivars as resistant genotypes [42,[56][57][58][59]. This study also demonstrated the extremely low frequency of Gro1-4 resistance-predictive allele within the subset of Russian potato cultivars.…”
Section: Introductionmentioning
confidence: 59%
See 3 more Smart Citations